Questionnaire for "The Programme Director and the Teaching Excellence Framework: How do we train the former to survive the latter?" - Massie, Ruth (Cranfield University, 2018)
This is the survey questions undertaken for "The Programme Director and the Teaching Excellence Framework: How do we train the former to survive the latter?" in Higher Education Quarterly.
Keywords: 'Programme Director'; 'Teaching Excellence Framework'; 'Business and Management not elsewhere classified'; 'Organisational Behaviour'; 'Higher Education'